Situated Learning in Interpreter Education From the Classroom to the Community - Miner, Annette; Nicodemus, Brenda; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This book bridges the gap between knowledge and real-world work experience by delineating a scaffolded curriculum that supports students trajectory toward authentic learning that maximally develops their interpreting skills. Kim B. Kurz, Associate Professor, Department of American Sign Language & Interpreter Education, National Institute for the Deaf at the Rochester Institute of Technology, USA This is a systematic, didactic, very readable handbook on interpreter training. The authors make a good case for situated learning, the underlying principle being the gradual introduction of aspects of authentic situations and challenges of real-life interpreting into the guidance of student interpreters being prepared for work in the field. Daniel Gile, Professor Emeritus, Université Paris Sorbonne Nouvelle, France This book provides a theoretical and pragmatic guide to the use of situated learning within structured interpreting programs. Proponents of situated learning theory believe that meaningful learning occurs when students interact with others in the social contexts in which they will be working. With such interactions, students have the opportunity to apply their theoretical knowledge to authentic contexts that they will encounter throughout their professional lives. While a limited number of research articles exist about the use of situated learning in interpreter education, this is the first full book to provide the foundations for situated learning theory, show how to implement situated learning in interpreter education, and offer practical applications for maximizing authenticity in interpreting classrooms. Annette Miner is an interpreter educator, curriculum developer, professional interpreter, and researcher. She has published on the topics of situated and experiential learning in interpreter education, curriculum design, and the role of designated interpreters. Brenda Nicodemus held the position of Professor and Director of the Center for the Advancement of Interpreting and Translation Research at Gallaudet University, USA, until retiring in 2020. Her research focuses on translation asymmetry in bimodal bilinguals, healthcare interpreting, and linguistic analysis of interpretation.
1. Introduction: Grabbing a Cat by the Tail -- 2. What is Situated Learning? -- 3. The Staircase Model for Interpreter Education -- 4. Situated Community Engagement -- 5. Situated Simulated Learning -- 6. Situated Authentic Interpreting -- 7. Mock Interpreting Scenarios -- 8. Partnerships and the Road Ahead.
Keywords: Teachers Training of; Education, Higher; Language and languages Study and teaching; Translating and interpreting; Sign language; Teaching and Teacher Education; Higher Education; Language Teaching and Learning; Language Translation; Sign Languages